Moringa Tofu PMT: Healthy Nutrition Alternative from Local Products for Karangkemiri Toddlers - Purnamasari, Laila; Mulia, Marina Aninditya; Syifa, Mukhammad Ibnu; Apriliani, Fadillah Eka; ’Aini, Afifah Qurrotu; Putri, Hilda Abelia Waluyo; Reyyan, Reyyan; Imanda, Firdha Wafa; Khoiriyah, Rizki Nur; Setiadi, Catur; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Stunting is a chronic nutritional problem that affects children’s physical growth, cognitive development, and future productivity. Karangkemiri Village, Karanganyar Subdistrict, Kebumen Regency, still faces a prevalence of stunting that requires appropriate nutritional interventions. This study aims to analyze dietary patterns among toddlers and develop an innovative local-based supplementary feeding (Pemberian Makanan Tambahan, PMT) product, Sempol Tofu with Moringa Leaves, as a stunting prevention effort. This descriptive quantitative research collected primary data through anthropometric measurements (weight and height) and questionnaires administered to mothers of toddlers. The sample consisted of 35 toddlers from RW 01 who received the PMT intervention. Survey results showed that most toddlers regularly consumed animal protein (92.6%), while intake of plant-based protein (48.1%) and iron-rich foods (37.0%) remained low. The Sempol Tofu with Moringa Leaves innovation combines plant-based protein (tofu) and micronutrients (moringa leaves), which are rich in vitamin A, iron, and calcium, and has the potential to improve toddlers’ nutritional status. This program not only increased mothers’ nutritional knowledge but also utilized affordable and easily processed local food ingredients. In conclusion, developing PMT based on tofu and moringa leaves can be an effective and sustainable strategy for preventing stunting at the village level.